Mapping of Scientific Production on Blended Learning in Higher Education - Mª Montserrat Castro-Rodríguez; Diana Marín-Suelves; Silvia López-Gómez; Jesús Rodríguez-Rodríguez (MDPI AG, 2021)
Blended learning is a set of pedagogical strategies and practices that are closely related to the emergence of new technologies in society and in higher education. They are characterized by a combination of face-to-face and online learning that integrates a variety of materials in the teaching and learning process. The aim of our research was to analyze scientific production on this topic using two prestigious international databases: Scopus and Web of Science (WOS). A bibliometric study was conducted on 508 papers, and content analysis was performed on 119 openly accessible publications. Results show that blended learning is being applied in all scientific and professional spheres. This learning model is praised for its positive impact on motivation and learning effectiveness, as well as for promoting student autonomy. With respect to content, it is worth noting that many authors observe that methodological success is related to cultural context and access to devices and materials. Furthermore, it is suggested that greater methodological diversity is preferable to a single hegemonic approach. In short, the present paper contributes to the educational community by shedding light on how blended learning is being implemented and its impact on higher education.